Design of small capacity meter with linear characteristic - K. K. Kim; A. A. Tkachuk; A. A. Kuznetsov (Омский научный вестник)
We consider the small-capacity meter with its technical and metrological characteristics in this paper. The diagram of the functional generator and the voltage timing diagrams are given to study operation of the functional generator. The issues of using a capacity meter during the measurement of the parameters of the railway transport devices are considered.